Release of lysosomal enzymes from kidney lysosomes in seronegative rheumatoid artritis - Dejan Spasovski (Archives of Clinical Nephrology - Peertechz Publications, 2020)
Introduction: To determine the effects of non-treated seronegative Rheumatoid Arthritis (RA) on proximal renal tubule, sensitivity of Alanine Aminopeptidase (AAP), γ-Glutamyltransferase (γ--GT), β2 Microglobulin in urine (β2M), as well as relation with Rheumatoid Factor (RF) and C-Reactive Protein (CRP), DAS 28 disease activity index. Methods: RF was determined by agglutination test (Latex) RF test, while kinetic methods were used for determination of Alanine Aminopeptidase (AAP) and γ-Glutamyltransferase (γ-GT), as well as MEIA (Microparticle Enzyme Immunoassay) to determine β2 microglobulin in urine. Samples (serum and urine) of 70 participants were examined (35 RA not treated, 35 health control group). Results: In 35 RF negative RA, AAP enzymuria was present in 12 (34.28%) patients, γ-GT was present in 7 patients (20%), while β2 microglobulin was present in 3 patients (8.57%). In the healthy control group, 4 patients showed AAP positivity (11.42%), 2 patients γ-GT positivity (5.71%) and 1 patient showed presens of b2 microglobulin in urine (2.85). RF was not present in any patient (0%). Conclusion: AAP has a higher sensitivity of γ-GT and b2 microglobulin in the detection of asymptomatic renal lesions in non trated seronegative RA.